The effect of natural antimicrobials against Campylobacter spp. and its similarities to Salmonella spp, Listeria spp., Escherichia coli, Vibrio spp., Clostridium spp. and Staphylococcus spp. (March 2021) - Balta, Igori; Linton, Mark; Pinkerton, Laurette; Kelly, Carmel; Stef, Lavinia; Pet, Ioan; Stef, Ducu; Criste, Adriana; Gundogdu, Ozan; Corcionivoschi, Nicolae
Abstract: The increased resistance of campylobacters to antibiotics required the identification and isolation of novel antimicrobials able to inhibit its virulence, to cause less or no resistance and display no host toxicity. Acquiring all this knowledge was only possible through a better understanding of their antibacterial potency and of the biological mechanisms involved attenuating the bacterial virulence factors. This review describes the most recent developments in the area by looking at the new antimicrobial interventions aiming to combat the transmission and colonisation of Campylobacter spp. and its commonalities with other pathogenic bacteria. In this review we are also looking into the most recent developments, both in vitro and in vivo, focusing on the biological mechanisms by which natural antimicrobials express their anti-pathogenic effect. Following this extensive literature search we conclude that further studies are essential to elucidate the efficiency of plant, animal, bacteria and marine-derived antimicrobials as well as their role as promising alternatives to antibiotics. Highlights: Impact on Campylobacter and other bacteria virulence genes expression. In vitro reduces attachment of bacteria to epithelial cells. In vivo reduces bacterial pathogen colonisation. Improves food safety and increases consumer confidence.